1998
DOI: 10.1038/sj.bjp.0701783
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of CGRP receptors mediating relaxation of the rat pulmonary artery and inhibition of twitch responses of the rat vas deferens

Abstract: 1 CGRP receptors mediating vasorelaxation of the rat isolated pulmonary artery and inhibition of contractions of the rat isolated prostatic vas deferens were investigated using CGRP agonists, homologues and the antagonist CGRP . 2 In the pulmonary artery, human (h)a-CGRP-induced relaxation of phenylephrine-evoked tone was abolished either by removal of the endothelium or by N G -nitro-L-arginine (10 75 M). The inhibitory e ect of N G -nitro-L-arginine was stereoselectively reversed by L-but not by D-arginine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 26 publications
(38 reference statements)
7
54
3
Order By: Relevance
“…In rat aorta [44] and pulmonary artery [45], CGRP interacts with endothelial receptors, stimulating the release of endothelium-derived relaxing factors. By contrast, in cat cerebral [46], pig coronary [47] and rat mesenteric vessels [48], CGRP acts directly on VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In rat aorta [44] and pulmonary artery [45], CGRP interacts with endothelial receptors, stimulating the release of endothelium-derived relaxing factors. By contrast, in cat cerebral [46], pig coronary [47] and rat mesenteric vessels [48], CGRP acts directly on VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP, a vasodilator neuropeptide, is widely distributed in the autonomic nerve terminals supplying the cardiovascular system and is present in plasma. 24,45,46 Recent studies 24,45,[47][48][49] have found that CGRP can also evoke endothelium-dependent and NO-mediated vasodilation. Adrenomedullin shares significant structural homology with CGRP.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptions to endothelium-independent relaxation to CGRP occur only in a few tissues, including the rat aorta, where the relaxation to CGRP depends on the presence of an intact endothelium and is attenuated by inhibitors of NO synthase, implying an NO-dependent mechanism [12,50]. In human internal mammary artery [51] and rat pulmonary artery [52], a similar endothelium-dependent mechanism of relaxation has also been seen. Evidence that CGRP activates phospholipase C in HEK293 cells, lead-ing to an increase in intracellular Ca 2+ via inositol trisphosphate (IP3) [53] suggests that this alternative intracellular pathway may be responsible for the CGRP-induced release of NO (Fig.…”
Section: Arterial Relaxation By Cgrpmentioning
confidence: 99%